The Big Bad Wolf Book Sale returns to Pahang - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd, 2020)
KUANTAN: Known as the World’s Biggest Book Sale, the Big Bad Wolf Book Sale is returning to Pahang from Feb 28 to March 9 at Universiti Malaysia Pahang’s Gambang Campus’ sports complex from 10am to 12 midnight daily.